Sudden rupture of small aneurysm of the radial artery in a patient with COVID‐19 pneumonia. Issue 6 (23rd June 2021) - Mazzaccaro, Daniela; Giannetta, Matteo; Malacrida, Giovanni; Zilio, Dino; Modafferi, Alfredo; Righini, Paolo; Marrocco‐Trischitta, Massimiliano M.; Vaienti, Luca; Nano, Giovanni
Abstract: In patients with COVID‐19, even small radial aneurysm may suddenly rupture. Abstract : In patients with COVID‐19, even small radial aneurysm may suddenly rupture.